The Mediating Effects of Attachment Styles on the Relationship between Sensory Processing Styles and Interpersonal Problems in Healthy University Students - Oan Na Lee; Gyeong-A Park (Hindawi-Wiley, 2020)
Purpose. Difficulties with sensory processing are known to have negative effects on individuals' attachment styles and the interpersonal domain. We investigated the relationships among sensory processing styles, attachment styles, and interpersonal problems to better understand the role of attachment styles on the relationship between sensory processing styles and interpersonal problems. Participants. One-hundred and eighty-four university students (aged 18-28 years) completed a set of self-reported measures. Methods. Sensory processing styles, attachment styles, and interpersonal problems were assessed with the Adolescent/Adult Sensory Profile, Experiences in Close Relationships-Revised, and Inventory of Interpersonal Problems-Short Circumplex Form, respectively. Results. Low registration (r=0.587, p<0.001) and sensory avoidance (r=0.501, p<0.001) were positively correlated with interpersonal problems. Regression analyses indicated that low registration (β=0.301, p<0.001) and anxious attachment (β=0.640, p<0.001) were predictors of interpersonal problems (R2=0.672, p<0.001), and sensation avoidance (β=0.386, p<0.001) and avoidant attachment (β=0.233, p<0.001) were predictors of interpersonal problems (R2=0.286, p<0.001). Participants with higher levels of low registration reported higher levels of interpersonal problems, and this relationship was partially mediated by anxious attachment. Participants with higher levels of sensory avoidance reported higher levels of interpersonal problems, and this relationship was partially mediated by avoidant attachment. Conclusions. This study clarifies the relationships between sensory processing styles and interpersonal problems and the mediating effects of attachment styles. The results were discussed in light of the related literature.